EFFECT OF VIRECHANA KARMA IN VICHARCHIKA WITH SPECIAL REFERENCE TO ECZEMA – A CASE REPORT - Rangasubhe Poornima; Umesh V. Purad; S.N.Belavadi (International Journal of Ayurveda and Pharma Research, 2019)
Panchakarma is a specialized branch of Ayurveda, which deals with both aspects of Ayurvedic treatment which are purification as well as pacification of vitiated Doshas. Virechana (Purgation) is considered as Agra Chikitsa (main treatment) in all types of Kushtarogas (skin diseases) and also given Pradhanyata in Pittaja type of Kushtas. Vicharchika is a type of Kshudra kushta with Pitta and Kapha dosha pradhanyata and has the symptoms like Kandu (itching), Srava (discharge), Pidaka (eruption) and Shyavavarna twacha (blackish discoloration of skin). Vicharchika is often correlated with Eczema based on its clinical presentation. Acharya Kashyapa mentioned it as Sadhya vyadhis (curable disease). The main line of treatment of Vicharchika is Shodhana (purification) and Shamana (pacification). Among the Shodhana karma, Virechana is chiefly advised along with Shamanaushadi. We are presenting a case of Vicharchika, who made a remarkable improvement in the condition with these lines of treatment.